2014
DOI: 10.1371/journal.pone.0088416
|View full text |Cite
|
Sign up to set email alerts
|

Unconscious Priming of Task-Switching Generalizes to an Untrained Task

Abstract: Evidence suggests that subliminal stimuli can influence ostensibly volitional, executive processes but it is unclear whether this is highly task-specific. To address this we used a set-switching task. Volunteers saw a word pair and reported either if both words had the same number of syllables or if both were concrete. Task selection was random and instructed by a hexagon/triangle preceding the words. A subliminally-presented square or diamond reliably preceded each of these consciously perceived instruction-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 15 publications
4
16
1
Order By: Relevance
“…Operant conditioning experiments revealed that subliminally presented stimuli helped to improve task performance if these stimuli reliably predicted which behavior would lead to success in the next trial (Pessiglione et al, 2008 ; Palminteri et al, 2009 ; Pine et al, 2014 ; Mastropasqua and Turatto, 2015 ). Similar results were obtained if initially irrelevant subliminal stimuli were repeatedly followed by a switch of tasks in task-switching experiments or were paired with specific target categories in priming experiments: with enough practice, participants improved on switch trials when subliminal cues had predicted the task switches (Zhou and Davis, 2012 ; Manly et al, 2014 ; Farooqui and Manly, 2015 ) and were faster at classifying targets that were predicted by a preceding subliminal prime (Custers and Aarts, 2011 ; Marcos Malmierca, 2015 ). Finally, dichoptic stimulation experiments showed that the repeated presentation of a sequence of subliminal events allowed participants to later identify this same sequence despite their inability to detect the underlying events (Rosenthal et al, 2010 , 2016 ).…”
Section: Introductionsupporting
confidence: 53%
“…Operant conditioning experiments revealed that subliminally presented stimuli helped to improve task performance if these stimuli reliably predicted which behavior would lead to success in the next trial (Pessiglione et al, 2008 ; Palminteri et al, 2009 ; Pine et al, 2014 ; Mastropasqua and Turatto, 2015 ). Similar results were obtained if initially irrelevant subliminal stimuli were repeatedly followed by a switch of tasks in task-switching experiments or were paired with specific target categories in priming experiments: with enough practice, participants improved on switch trials when subliminal cues had predicted the task switches (Zhou and Davis, 2012 ; Manly et al, 2014 ; Farooqui and Manly, 2015 ) and were faster at classifying targets that were predicted by a preceding subliminal prime (Custers and Aarts, 2011 ; Marcos Malmierca, 2015 ). Finally, dichoptic stimulation experiments showed that the repeated presentation of a sequence of subliminal events allowed participants to later identify this same sequence despite their inability to detect the underlying events (Rosenthal et al, 2010 , 2016 ).…”
Section: Introductionsupporting
confidence: 53%
“…Thus, the learning of associations involving subliminal and incidental perceptual events in the task environment is better than associations involving more visible events (Watanabe et al 2001;Tsushima et al 2006Tsushima et al , 2008Farooqui & Manly, 2015). Likewise, subliminal events presented during the execution of an ongoing task frequently results in stronger priming effects than more visible events (Lau & Passingham, 2007;Zhou & Davis, 2012;Manly et al 2014;Lin & Murray, 2015). Arguably, in such cases more visible events are more accessible to attentional mechanisms that put stronger limits on their processing compared to the case with subliminal events.…”
Section: Attentionmentioning
confidence: 99%
“…The studies presented in this article examined whether predictive information contained in subliminal cues could be used to potentiate goal-directed cognitive control. As a result of past associations or explicit knowledge, subliminal presentation of a stimulus can influence cognition by activating perceptual processes (Bar & Biederman, 1998), semantic processes (Draine & Greenwald, 1998), or even control-related processes (e.g., task set, response inhibition, and attentional shift) linked to the stimulus (Lau & Passingham, 2007;Manly et al, 2014;Reuss, Kiesel, Kunde, & Wühr, 2012;van Gaal & Lamme, 2012). However, such activations tend to be reflexive: When the necessary conditions are fulfilled , the subliminal stimulus activates its linked process regardless of its relevance to the goal.…”
Section: Research Articlementioning
confidence: 99%